Anadolu Araştırmaları IV-V (1976-77). İstanbul Üniversitesi Edebiyat Fakültesi Eski önasya Dilleri ve Kültürleri Kürsüsü ile Eskiçağ Tarihi Kürsüsü tarafından Yayınlanır (2012)
Anatolian Researches; Published by the Cathedra for Ancient Near Eastern Languages and Cultures and the Cathedra for the History of Antiquity of the Faculty of Letters of the Univ. of Istanbul.